“Nutritional Habits and Factors Affecting Food Consumption Patterns among Urban Dwellings in Cairo - Egypt” - Nashaat, Nahla Ali Maher; Shalaby, Silvia Farouk (International Journal of Innovative Research in Medical Science, 2019)
Socioeconomic status (SES) is a major determinant of health in high-income countries(HICs) and low and middle-income countries(LMICs)[1-4]. Contrary to HICs, only a few studies have documented the social patterning of diet in LMICs.[1-5] The current study was conducted aiming to investigate the nutritional habits of urban households and the effect of the increase in food prices on consumption patterns; in addition to their response and coping methods. Methodology: Cross – sectional community based descriptive study was used. Demographic data were described. A simple random sample of 400 adults, 264 males & 136 females aged between (20-50 years old) living in Cairo; were included through a period of 4 months. Results: Food consumption between the years 2015& 2017 within all food items (P<0.0001) showed statistically significant difference. The parents’ education and occupation had a significantly positive effect on the dietary habits of their families. Conclusion: There is a trend in recent time of world food price increase and changing of consumption pattern especially in emerging developing economies. Therefore, this study recommends applying food price policies to reduce the effects of food price fluctuation. In addition to raising awareness about healthy nutritional habits.